Tracking the Changes. - Huijts, Stijn; Jongewaard, Roxy (Maastricht : Bonnefanten, 2021)
Angelista, Serana ; Chan, Kent ; Elstak, Brian ; Gario, Quinsy ; Haifeng, Ni ; Van Haver, Raquel ; van Houwelingen, Hans ; Jong, Alle ; Joseph, Kahlil ; Kaersenhout, Patricia ; Marshall, Kerry James ; Nguyen, Tuan Andrew ; Nkanga, Otobong ; Saar, Alison ; Saar, Betye ; Sadée, Juul ; Taylor, Henry ; Zwarts, Kim
Say It Loud, Bonnefanten, Maastricht, 29 september 2020 tot en met 18 april 2021
boek